Edukasi Kesehatan untuk Meningkatkan Kualitas Hidup Pada Kelompok Lanjut Usia - Meiyanti; Yohana; Margo, Eveline; Kartadinata, Erlani; Sisca; Hartanti, Monica Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The increase in the elderly population raises concerns regarding the potential lack of understanding of chronic illnesses in this age group and their impact on quality of life. The main objective of this initiative is to provide education on a better understanding of the health issues faced by the elderly and how to manage them effectively. The study was conducted in November 2023 with 25 participants involved: 1) Preparing educational materials, 2) Providing education to elderly caregivers, and 3) Evaluating the impact of these activities through pre-and post-tests. As a result of the study, an increase in knowledge about various health problems and strategies to improve the quality of life of the elderly was observed after receiving education. As part of this activity, health status examinations were conducted, and the quality of life of elderly individuals was assessed using questionnaires. It was found that 52% of the participants reported suffering from hypertension, heart disease, or metabolic endocrine diseases. It is worth noting that the physical domain had the lowest quality-of-life score compared to other domains. In conclusion, it could be argued that community health education activities may play a crucial role in enhancing the quality of life of the elderly by equipping them with the necessary knowledge and skills to manage their health challenges